2015
DOI: 10.3892/ol.2015.4007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of NHERF1 through RNA interference inhibits the proliferation and migration of metastatic prostate cancer cells

Abstract: Abstract. The present study aimed to investigate the effects of Na + /H + exchanger regulatory factor 1 (NHERF1) gene knockdown, using short-hairpin RNA (shRNA), on the malignant behaviors of prostate cancer cells. A pSuper.puro NHERF1 shRNA vector was transfected into PC-3M prostate cancer cells using Lipofectamine 2000. Stable cell lines were obtained and NHERF1 knockdown was verified through western blot analysis. MTT assays were then used to measure PC-3M cell proliferation; in addition, cell migration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Regarding NHERF-1, this scaffolding protein has been involved in both tumor progression and inhibition in different types of cancer [20,[32][33][34][36][37][38][39][40][41][42][43][44][45][46]. Our data show a decrease in NHERF-1 immunolabeling in primary human prostate tumors compared to control samples.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Regarding NHERF-1, this scaffolding protein has been involved in both tumor progression and inhibition in different types of cancer [20,[32][33][34][36][37][38][39][40][41][42][43][44][45][46]. Our data show a decrease in NHERF-1 immunolabeling in primary human prostate tumors compared to control samples.…”
Section: Discussionmentioning
confidence: 56%
“…Stabilization of β-catenin at cellular junctions in murine embryonic fibroblast models is also potentially induced by NHERF-1 [ 39 ]. Although these features are indicative of a tumor suppressor function, NHERF-1 has been involved in both tumor progression and inhibition [ 20 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. An immunohistochemical study in prostatic cancer has revealed decreased NHERF-1 presence in primary and metastatic prostatic adenocarcinoma samples [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…EBP50 has various roles in cellular functions of cancer cells, in addition to modulating transporter activity. For example, EBP50 affects cellular proliferation and trafficking [ 16 , 17 ], and oncogene activation [ 18 ]. Therefore, inhibiting EBP50 may have additional effects on cancer cells, depending on their type.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular leucine rich repeat and fibronectin type III domain-containing 2/protein phosphatase 1 regulatory subunit 29 putative oncogene, hypomethylation gene [113] overexpressed in GC tissues and cell lines [114]; oncogene in GBM [113] AT interacts with AurkA and eukaryotic translation initiation factor 2 subunit alpha (EIF2α) and regulates the kinase activity of AurkA to promote cell autophagy [113] knockdown inhibits cell proliferation, migration, invasion, increases E-cadherin and decreases N-cadherin [114] SLC9AR1/ NHERF1/ERB50 Solute carrier (SLC) family 9 (Na(+)/H(+) exchanger), member 3 regulator 1/sodium-hydrogen exchanger regulatory factor 1/ERM-binding phosphoprotein multifunctional cytoplasmic adaptor involved in growth factor signaling [115]; interacts with several proteins related to the estrogen pathway and tumorigenesis: EGFR, PTEN, PDGFR, beta catenin, EZR [116] in BC acts as a tumor suppressor protein; oncogene in glioma and other cancers; overexpressed in PCa tissue and cell lines [117] AT/PT MTORC1_SIGNALING; ESTROGEN_RESPONSE_LATE; downregulation is associated with Wnt/β-catenin inactivation [118]; knockdown enhances PDGF-induced cytoskeletal rearrangements and chemotactic migration of cells [119]; AKT-associated protein [115] knockdown suppresses proliferation and migration of metastatic PCa cells and promotes apoptosis [117] LGG-low grade glioma; LSCC-lung squamous cell carcinoma; LUAD-lung adenocarcinoma; LUSC-lung squamous cell carcinoma; MAPK-mitogen-activated protein kinase; MDM2-mouse double minute 2 homolog/E3 ubiquitin-protein ligase; MM-malignant mesothelioma; MMP9-metalloproteinase 9; mTOR-mammalian target of rapamycin; NOX1-NADPH oxidase 1; NPC-nasopharyngeal carcinoma; NSCLC-non-small-celllung cancer; OCCC-ovarian clear cell carcinoma; OSCC-oral squamous cell carcinoma; OXPHOS-oxidative phosphorylation pathway; PCC-pancreatic cancer; PCa-prostate cancer; PDAC-pancreatic ductal adenocarcinoma; PT-pro-tumorigenic; PTEN-phosphatase and tensin homolog; ROS-reactive oxygen species pathway; TC-testicular cancer; TCA-tricarboxylic acid; TGF-β-transforming growth factor beta; uLMS-uterine leiomyosarcoma; UPR-unfolded protein response; VIM-vimentin.…”
Section: Nckap1/nap1mentioning
confidence: 99%